Eleny Makarovej droga do arteterapii - Pawletko, Beata (Studia Rossica Posnaniensia, 2026)
The aim of the article is to review Elena Makarova’s art therapy practices, which, apart from commemorating the Holocaust, are the main hallmark of her creative activity. Interestingly, it was only after discovering the history of the Terezin Ghetto that Makarova became convinced that the path she followed in the USSR, her methods of work and pedagogical observations, which were implemented after a two-year stay at the Turist hospital, they have much in common with how the Austrian artist Friedl Dicker-Brandeis worked with children in Theriesenstadt, as well as with the beliefs of Friedl’s student, Edith Kramer, who became one of the forerunners of art therapy alongside Margaret Naumburg. Having decided to move from the USSR to Israel, Makarova uses art therapy not only in working with people with disabilities, but also victims of modern armed conflicts, including war refugees from Ukraine.